Snacks for the soul : snacks for the soul is a collection of stories that offer emotional, intellectual and spiritual nourishment - Vaswani, J.P (Snergymedia, 2007)
Snack for the soul is a collection of stories that offer emotional, intellectual and spiritual nourishment